Effects of the crosslinking of chitosan/DCPA particles in the antimicrobial and mechanical properties of dental restorative composites - Kikuchi, Lucia Nobuco Takamori; Freitas, Selma Regina Muniz; Amorim, Aldo Ferreira; Delechiave, Giovanne; Catalani, Luiz Henrique; Braga, Roberto Ruggiero; Moreira, Maria Stella; Boaro, Leticia Cristina Cidreira; Gonçalves, Flávia (Dental materials, 2022)
The development of restorative materials containing antibacterial agents is an alternative to reduce the progression of caries lesions. to compare the influence of the degree of crosslinking of chitosan particles loaded with dibasic calcium phosphate (DCPA) on the mechanical properties, degree of conversion (DC), and antimicrobial properties of experimental composites. Chitosan/DCPA particles were synthesized by the electrospraying, crosslinked by 0, 8, or 16 h in glutaraldehyde, and characterized by zeta potential and minimum inhibitory concentration (MIC) against S. mutans. Experimental resin composites of Bis-GMA and TEGDMA and 59.5% of barium glass were synthesized, chitosan/DCPA particles were added at 0 or 0.5 wt% with the different crosslinking time. The materials were subject to DC analysis, three-point bending test at 24 h and 7 days, and antimicrobial assays. Data were submitted to one-way ANOVA and Tukey test (α = 0.05). The particles with longer crosslinking time presented higher zeta potential and MIC, and the composite containing these particles showed significantly higher biofilm inhibition than the control group. The other two groups were similar to each other and the control. The composite containing particles with 88 h crosslinking time showed the lowest flexural strength at 7 days in water, and materials with non-crosslinked particles and longer crosslinking time presented flexural strength similar to control. The flexural modulus and DC showed no statistical difference among groups. composite resin containing 0.5% chitosan/DCPA particles crosslinked by 16 h showed a reduction of biofilm formation without affecting the mechanical properties in relation to the control. •Crosslinking of chitosan particles increases the minimum inhibitory concentration.•The composite with longer crosslinking time presented higher biofilm inhibition.•The composite with longer crosslinking time maintain the mechanical properties.•The resin composite with longer crosslinking maintain the conversion.